2019
DOI: 10.3935/rsp.v26i2.1593
|View full text |Cite
|
Sign up to set email alerts
|

Listening to a Silent Crisis: Men’s Suicide in Rural and Farming Communities in Slovenia

Abstract: The rate of suicide remains high in Slovenia, particularly in rural settings and among farmers. As is the case with many issues faced by rural people, few social responses are developed in terms of political action, health and social services and research. In this article, the severity of farmers' suicide in Slovenia is detailed and analysed as a social problem based on the following criteria: first, the scope of the situation is considered worrying and unequal; second, normative structures are abnormally or h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…Inevitably, this conflicted with any proposition to prioritize health needs or to show vulnerability and seek help. For most farmers in this study, health was seen as “women’s business,” with feminine connotations, and not something “hard-working men” had time to engage with ( Roy & Hočevar, 2019 ). Notably, some farmers contested such framings, extolling the virtues of a more responsible and proactive approach to health over more stoic and reactive approaches.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Inevitably, this conflicted with any proposition to prioritize health needs or to show vulnerability and seek help. For most farmers in this study, health was seen as “women’s business,” with feminine connotations, and not something “hard-working men” had time to engage with ( Roy & Hočevar, 2019 ). Notably, some farmers contested such framings, extolling the virtues of a more responsible and proactive approach to health over more stoic and reactive approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in a Canadian context, Roy et al (2017) found that farmers often sacrificed rest in favor of a “relentless worker” model to uphold their masculine image. Roy and Hočevar (2019) note how farmers are continually negotiating health practices in relation to hegemonic masculinity; and that “doing health” is a form of “doing gender.” Indeed, the act of opposing health-enhancing behaviors or help-seeking behavior could be seen as an active demonstration of manliness for some farmers and a rejection of the more feminine connotations of weakness and stigmatization associated with health ( Ní Laoire, 2005 ; Roy et al, 2014 , 2017 ). In this sense, the cultural influences that shape farmers’ beliefs, attitudes, and practices are synonymous with the pursuit of a hegemonic form of farming masculinity that can be demonstrated in the avoidance of behaviors that show concern for health or that require emotional expression or help-seeking on the basis that such practices might position farmers as weak or vulnerable ( Cleary, 2012 ; Ní Laoire, 2005 ; Roy et al, 2017 ; Verdonk et al, 2010 ).…”
Section: Farming Identities and Farming Masculinitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…While farmers are sometimes romantically thought of as enjoying a traditional ‘way of life’ immersed in bucolic surroundings, the reality can be radically different and the cost of such benefits high. Elevated levels of stress, physical injury and suicide have long been reported within the industry across the developed world (Arnautovska et al., 2015; Bossard et al., 2016; Earp, 2007; Firth et al., 2007; Furey et al., 2016; Hawton et al., 1998; Roy & Knežević Hočevar, 2019; Stark et al., 2006). The issue has received particular attention in Australia (e.g., Alston, 2012; Bryant & Garnham, 2015, 2014; Peel et al., 2016; Perceval et al., 2017) and the US (e.g., Ramos et al., 2016; Ringgenberg, 2014; Roy et al., 2017) where a comprehensive body of research has highlighted the importance of understanding and addressing the nuances and complexities of a myriad of stressors affecting farmers and their families.…”
Section: Farming and Mental Healthmentioning
confidence: 99%